Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content: 1. The quality of accounting information in light of the impact of the use of cloud computing An exploratory study of the opinions of a sample of academics and professionals in Iraq Teacher Ahmed Hssein Machi , Teacher Murtadha Saleh Mahdi , Asst-Teacher Ali Noori Abdulzahr 2. The impact of the quality of health services on the loyalty of health insurance clients in the state of Jazeera-Sudan Dr. Amani Abdelatti Omer Alsheekh, Dr. Muhsin Mohammed Gasmalla Ali 3. Assessing the application of International Accounting Standards for small and medium-sized Enterprises in Oman Dr. Ashraf Abdullateef Abdulrahman Mukhtar 4. The impact of strategic planning on knowledge sharing in the Salah Al-Din Health Department in Iraq from the point of view of administrative leaders 2022 Asst-Teacher. Anas Khleel Mahdi1 , Co-Prof. Elfadil Timan Idriss1 , Co-Prof. Malikelneem Muhammad Ali1 5. The Role of The Joint Audit in Reducing the audit expectations gap - A field study Co-Prof. Bashir Bakri Agib Babiker 6. The role of custom in controlling discretionary exchange issues in contemporary financial transactions Dr. Abed Alrahem Ahmed Alsahhar 7. Turkey and the chances of membership in the European Union and the future of the relationship 1950-2015 Dr. Mohammad Mahmoud Tabtab , Dr. Wesal Abdullah Mohammed Saleh 8. Foreign Direct Investment and its Impact on Value Added in the Industrial Sector of the Kingdom of Saudi Arabia Dr. Vivian Mohammed Saleh Nasrulddin , Dr. Sahar Hassan Khayat , Mrs. Maha Ahmed Alharbi 9. The Supervisory Role of Labor Inspection in the Control of Labor Violations Mrs. Alotaibi Mead Mohammed 10. The Effect of Organizational Climate on Organizational Commitment in 2022: Case Study - Gaza Electricity Distribution Corporation Mr. Wasim M. H. Swidan , Dr. Kalsom Binti Ali , Dr. Ali Nasser Al-Tahitah